"The Economist and the State"–An Addendum - Buttrick, John (Review of Economic Studies, 1950)
Journal Article “The Economist and the State” — An Addendum Get access John Buttrick John Buttrick Evanston, Illinois Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 18, Issue 3, 1950, Pages 190–192, https://doi.org/10.2307/2295980 Published: 01 September 1950